The effect of tooth wear, age and sex on facial height assessed by soft tissue analysis - Levartovsky, Shifra; Aharonov, Olisya; Emodi Perlman, Alona; Winocur, Ephraim; Sarig, Rachel (Journal of oral rehabilitation, 2020)
Aim The aim of the study was to evaluate the effects of tooth wear, age and sex on facial height measurements based on soft tissue analysis. Methods One hundred and twelve subjects (45 males and 67 females), 19‐80 years of age (mean 43 ± 0.9 years), which were divided into three age groups, met the inclusion criteria. Tooth wear was assessed using a 5‐point ordinal scale (0‐4). Based on the tooth wear score, three groups were defined: mild, moderate and severe wear. Facial height was evaluated based on soft tissue measurements using frontal facial photographs. The dimension of the upper facial height (UFH) and lower facial height (LFH) and the ratio between the two (R‐U‐L) were measured. Results Facial height dimensions (UFH, LFH) were significantly different between the three age groups and between the three tooth wear groups. Both the UFH and LFH measurements had a weak positive correlation with age (r = .40; r = .41, respectively) and with tooth wear (r = .40; r = .41, respectively). The R‐U‐L showed a significant difference (P < .001) between sexes as males showed slightly lower ratio compared with females; however, the R‐U‐L was not dependent upon age or tooth wear. Conclusions This study demonstrated that although facial height is affected by age and tooth wear, the proportion between the upper to lower facial segments is constant and is not affected by the same parameters. A statistically significant difference in the R‐U‐L relative to sexes was noted.